(untitled) (Fractal: Journal of Psychology, 2009)
In the city where we live each one of us usually goes to those places that have a special meaning. All these places describe one’s map of the city. But the use of the city depends above of all on the social standing of a person.Before, it was considered the city map of patients discharged from psychiatric hospitals to understand the impact of deinstitutionalization . Today , it is necessary to consider the underground life of "illegal" immigrants in Italian cities. Their maps describe the social mechanism of refusal or acceptance. This helps us understand how people refuse to budge from their respective standpoints or on the contrary how the identities interact with each other and change. The choice results from the individual receptivity, but above all from human rights policies.